Pengaruh Konflik Kerja dan Stress Kerja terhadap Kinerja Karyawan pada PT. Jasa Raharja (Persero) Cabang Sumatera Utara - Tiyanus Hulu; Jakaria Sihombing; Toman Sony Tambunan (PT PUSTAKA CENDEKIA GROUP, 2024)
This research aims to investigate the influence of work conflict and work stress on employee performance in the context of the work environment. Data was collected through surveys and interviews with employees from various industrial sectors. The research results show that there is a significant relationship between the level of work conflict and work stress and employee performance. High work conflict tends to reduce employee performance, while high levels of work stress also have a negative impact on performance. Factors such as social support, conflict management, and stress management programs emerge as mitigating factors that can help improve employee performance in dealing with work conflict and stress. These findings have important implications for human resource management in efforts to improve employee well-being and productivity in challenging work environments.